PERMINTAAN DAN PENAWARAN MINYAK GORENG SAWIT INDONESIA - Khoiru Rizqy Rambe; Nunung Kusnadi (Forum Agribisnis, 2018)
In the last 15 years, Indonesia palm-cooking oil price tend to increase significantly. The increase of palm-cooking oil price was driven by either its demand or supply. This study aimed to determine factors affecting of demand, supply, and Indonesia palm-cooking oil price. This research used time series data from 1990 to 2014. Simultaneous equation model was performed to analyse demand and supply of palm-cooking oil. The result indicated that income and population significantly influenced demand for palm-cooking oil. These implied that palm-cooking oil is categorized as normal good and staple food in Indonesia. While the price of palm-cooking oil, palm oil production, and real price of CPO Domestic significantly influenced supply of palm-cooking oil. Indonesia palm-cooking oil price was not significantly affected by its demand and supply.